Corticosteroid-sparing topical treatment with cyclosporin for juvenile keratoconjunctivitis - Amarilla Barcsay-Veres; Anita Csorba; Illes Kovacs; Laszlo Tothfalusi; Otto Alexander Maneschg (Scientific Reports)
Abstract Ocular surface inflammation due to allergy and blepharitis can lead to corneal complications and visual impairment. The aim of this study is to evaluate the efficacy of a cyclosporin 0.1% topical treatment achieving steroid-sparing. Eighty pediatric patients with moderate and severe vernal and blepharitis-related keratoconjunctivitis were included. Symptoms (photosensitivity, itching, discharge, tearing), signs (corneal fluorescein staining, papillary hypertrophy) and patients’ subjective assessment were evaluated during a 6-month follow-up. At the follow-up, all patients treated with topical cyclosporin showed a significant improvement in all subjective symptoms and objective signs (p < 0.001). The total number of courses of rescue steroids courses decreased from 3.71 ± 1.72 to 0.25 ± 0.49 at month 3 and to 0.13 ± 0.38 dropping bottle at month 6 (p < 0.001 at both time points). The 96.1% of the allergic cohort and 96.4% of the blepharitis cohort experienced a satisfactory good or rapid and good effect during the 6-month follow-up. The probability of needing rescue corticosteroids increased with an odds ratio of 1.98, (95% CI: 1.19–3.28, p = 0.008) for each unit increase in Oxford score when analysing the whole cohort. Topical cyclosporin seems to be very effective reducing the number of recurrences of corneal involvement and the need for steroid treatment.